2017
DOI: 10.1089/neu.2016.4601
|View full text |Cite
|
Sign up to set email alerts
|

Nor-Binaltorphimine Blocks the Adverse Effects of Morphine after Spinal Cord Injury

Abstract: Opioids are frequently used for the treatment of pain following spinal cord injury (SCI). Unfortunately, we have shown that morphine administered in the acute phase of SCI results in significant, adverse secondary consequences including compromised locomotor and sensory recovery. Similarly, we showed that selective activation of the j-opioid receptor (KOR), even at a dose 32-fold lower than morphine, is sufficient to attenuate recovery of locomotor function. In the current study, we tested whether activation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 66 publications
1
11
1
Order By: Relevance
“…However, the behavioural changes in response to chronic morphine treatment are independent of MOP receptor, cyclin-dependent kinase 5 (cdk5) or adenylyl cyclase activities in relevant areas of the brain [216]. Studies suggested that the morphine-induced behavioural effects are probably derived from its binding to the KOP receptor but not to the MOP receptor [217,218]. The likely multiple mechanisms that link chronic morphine treatment to its behavioural effects are not completely understood but may be controlled by a combination of dopaminergic, GABAergic, opioidergic and additional unknown neuronal signals [107,[202][203][204][212][213][214].…”
Section: Other Adverse Effectsmentioning
confidence: 99%
“…However, the behavioural changes in response to chronic morphine treatment are independent of MOP receptor, cyclin-dependent kinase 5 (cdk5) or adenylyl cyclase activities in relevant areas of the brain [216]. Studies suggested that the morphine-induced behavioural effects are probably derived from its binding to the KOP receptor but not to the MOP receptor [217,218]. The likely multiple mechanisms that link chronic morphine treatment to its behavioural effects are not completely understood but may be controlled by a combination of dopaminergic, GABAergic, opioidergic and additional unknown neuronal signals [107,[202][203][204][212][213][214].…”
Section: Other Adverse Effectsmentioning
confidence: 99%
“…Not surprisingly, there was a main effect of surgery on CD86 expressing macrophages, with contused rats exhibiting signi cantly higher numbers of CD86+ macrophages than shams on Day 7 post injury (F (1, 20) = 16.07, p < 0.001, Figure 7C). Additionally, we previously found that activation of KORs is both su cient and necessary to mediate the negative effects of morphine on motor recovery in the rat model of SCI [12,13]. To explore whether morphine administration altered the expression of opioid receptors on speci c subpopulations of immune cells we quanti ed KOR expression within the CD86+ subpopulations of microglia and macrophages.…”
Section: Assessment Of Opioid-induced Hyperalgesiamentioning
confidence: 99%
“…Our data from a rat SCI model suggests that opioid administration causes acute and long-term pain, rather than a correlative association with higher pain leading to greater opioid use. In the rat model, our laboratory has repeatedly found that morphine given in the days following the injury signi cantly undermines locomotor function, increases cell death around the lesion, and increases chronic pain [7][8][9][10][11][12][13][14][15]. Given the limited number of effective analgesics, it is critical that we develop a better understanding of the molecular consequences of activating opioid receptors within the highly in ammatory context of SCI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last two years, many research studies, focusing on the identification of drugs potentially effective in SCI treatment, have been published [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ,…”
Section: Overview Of Current Pharmacological Approaches For the Trmentioning
confidence: 99%